The Effect of Using Free Writing Technique on Students’ Writing Recount Text Ability in An Islamic Boarding School - Ayu Wulandari (Nalar Global, 2020)
This study aims to find out whether there is a significant effect of using free writing technique on students’ ability in writing recount text. It was carried out in the design of quasi-experimental research. The sample of this research was tenth-grade EFL students which were divided into control class and experimental class. Each class was provided with pre-test, treatment, and post-test. In collecting the data the researcher used writing test to measure the students’ ability to write recount text. Two professional raters were involved to score the students’ writings. The collected data were analyzed through T-test formula. Based on the findings, it can be concluded that the students’ ability in writing recount text is significantly improved after being taught by using free writing technique. Thus, teaching EFL students by using free writing technique is one of the solutions for the English teachers who want to improve their students’ ability in writing, especially for recount genre.